Print Ads and Sexist Appeal: The Portrayal of Women in American Men’s Apparel Ads From The 1950s-1970s - Hikmah, Noor; Munandar, Aris (Celt: A Journal of Culture, English Language Teaching & Literature, 2022)
Postwar American society developed severe views on how men and women should behave, with family structure being the best way to grow the nation. In the 1950s, 1960s, and 1970s, print ads depicted women as housewives, feminine, self-conscious, and eager to please their spouses. Print ads deceived women by persuading them that appearance and seductive attractiveness in real life were what counted. Women's bodies became objects, which might desensitize them and normalize sexism. The American male-dominated culture shapes and reflects print ads' portrayals of women. American print ads have shaped society by leveraging real-world symbols to convince consumers that the products they see are part of their lives. This research is methodically analyzed using the feminist theory of Betty Friedan (1963) and the gender theory of Erving Goffman (1979) to examine how women are portrayed and how sexism is depicted in 30 selected American men’s apparel print ads from the 1950s–1970s. The results found that American print ads developed a sense of pride in women’s efforts to maintain the house or prioritize the requirements of their partner. Women have been portrayed as everything from incompetent to sexual objects. They expected to find fulfillment in a society of masculine dominance.